Poria cocos polysaccharide—functionalized graphene oxide nanosheet induces efficient cancer immunotherapy in mice - Yang, Jinning; Dong, Xiaoxiao; Li, Boye; Chen, Tian; Yu, Boyang; Wang, Xiaoli; Dou, Xiangnan; Peng, Bo; Hu, Qin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Tumor vaccines that induce robust humoral and cellular immune responses have attracted tremendous interest for cancer immunotherapy. Despite the tremendous potential of tumor vaccines as an effective approach for cancer treatment and prevention, a major challenge in achieving sustained antitumor immunity is inefficient antigen delivery to secondary lymphoid organs, even with adjuvant aid. Methods: Herein, we present antigen/adjuvant integrated nanocomplexes termed nsGO/PCP/OVA by employing graphene oxide nanosheet (nsGO) as antigen nanocarriers loaded with model antigen ovalbumin (OVA) and adjuvant, Poria cocos polysaccharides (PCP). We evaluated the efficacy of nsGO/PCP/OVA in activating antigen-specific humoral as well as cellular immune responses and consequent tumor prevention and rejection in vivo. Results: The optimally formed nsGO/PCP/OVA was approximately 120–150 nm in diameter with a uniform size distribution. Nanoparticles can be effectively engulfed by dendritic cells (DCs) through receptor-mediated endocytosis, induced the maturation of DCs and improved the delivery efficiency both in vitro and in vivo. The nsGO/PCP/OVA nanoparticles also induced a significant enhancement of OVA antigen-specific Th1 and Th2 immune responses in vivo. In addition, vaccination with nsGO/PCP/OVA not only significantly suppressed tumor growth in prophylactic treatments, but also achieved a therapeutic effect in inhibiting the growth of already-established tumors. Conclusion: Therefore, this potent nanovaccine platform with nanocarrier nsGO and PCP as adjuvants provides a promising strategy for boosting anti-tumor immunity for cancer immunotherapy.